Analysis of Performance on Road Section RSAI–UNINUS Soekarno Hatta Highway Bandung Base on Traffic Flow Characteristic - Akbardin, Juang; Ma’soem, Dadang Mohamad; Rahmat, Fani Luthfiani Nur (Universitas Ibn Khaldun Bogor, 2024)
Population growth and private vehicle ownership can affect traffic conditions, the economy, and so on. If this condition is allowed and occurs continuously, the government will experience obstacles in the economy and the community will pay for travel costs which are increasing every year. So it is necessary to calculate the performance of the road. According to the calculation, the slow lane tends to have a poor level of road service, for the highest saturation degree value with a value of 0.98 found in the slow lane, the 2nd research point, and the direction road from RSAI to UNINUS, the saturation degree value of 0.95 is included in the service level (E) which is an unstable current where the current has faltered. For side barriers for the direction from RSAI to UNINUS has a very high class or a very high side resistance class, while for the direction from UNINUS to RSAI has a low side resistance class. For the average free current speed LV = 47.85 km / h; HV = 41.76 km/h; MC = 39.15 km/h. While for the existing speed has an average speed MC = 50.42 km / h; LV = 32.85 km/h; HV 2 AS = 36.41 km/h and HV 3 AS = 34.62 km/h. For the longest queue time of 0.00745 hours or 0.4464 minutes.